Hubungan Kreativitas Mengajar Guru Pendidikan Agama Kristen Dan Budi Pekerti Dengan Keaktifan Belajar Siswa Kelas XI SMA Swasta HKBP 2 Tarutung Tahun Pembelajaran 2023/2024 - Binur Panjaitan; Oktober Tua Aritonang; Lince Sihombing; Wilson Simanjuntak; Helena Putri Sibarani (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The aim of this research is to determine the relationship between Christian Religious Education Teachers Teaching Creativity and Character and the Learning Activeness of Class XI Students at HKBP 2 Tarutung Private High School for the 2023/2024 Academic Year. The method used in this research is a descriptive quantitative research method. The population was all class Data was collected using a positive closed questionnaire with 43 items, namely 30 items for variable X and 13 items for variable Y. The results of data analysis showed that: 1) A positive relationship test obtained a value rxy = 0,470 > rtable(=0,05,n=42) = 0,304 thus it is known that there is a positive relationship between variable X and variable Y. 2) A significant relationship test was obtained nilai tcount= 3,371 > ttable(=0,05,dk=n-2=40)=2,021 Thus there is a significant relationship between variable X and variable Y. So it is known that there is a positive and significant relationship between the Teaching Creativity of Christian Religious Education Teachers and Character and the Learning Activeness of Class XI Students of HKBP 2 Tarutung Private High School for the 2013/2024 Academic Year: Thus Ha is accepted and H0¬ is rejected.